2011
DOI: 10.1002/jnr.22790
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory role of zinc during aluminium‐induced altered carbohydrate metabolism in rat brain

Abstract: Aluminium is considered an environmental neurotoxicant and causes many neurological disorders, whereas zinc is vital for many biological functions. The present study was carried out to investigate the role of Zn, if any, in mitigating the adverse effects inflicted by Al on carbohydrate metabolism in rat brain. Male Sprague-Dawley rats weighing 140-160 g were divided into four different groups: normal control, Al-treated (100 mg/kg b.w./day in drinking water via oral gavage), Zn-treated (227mg/liter in drinking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 51 publications
(50 reference statements)
3
18
0
Order By: Relevance
“…This increase in 14 C‐glucose uptake indicates the increase in the requirement for glucose by neurodegenerative cells following Al treatment. These observations are well supported by our carbohydrate metabolism and histology findings, which also showed glucose‐deficient conditions in Al‐induced degenerative neurons (Singla and Dhawan, ). Furthermore, this trivalent metal has a pro‐oxidant activity, so it could have triggered oxidative stress either directly or indirectly by interacting with various proteins and molecules involved in energy metabolism (Yoshino et al, ; Gómez et al, ).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…This increase in 14 C‐glucose uptake indicates the increase in the requirement for glucose by neurodegenerative cells following Al treatment. These observations are well supported by our carbohydrate metabolism and histology findings, which also showed glucose‐deficient conditions in Al‐induced degenerative neurons (Singla and Dhawan, ). Furthermore, this trivalent metal has a pro‐oxidant activity, so it could have triggered oxidative stress either directly or indirectly by interacting with various proteins and molecules involved in energy metabolism (Yoshino et al, ; Gómez et al, ).…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, high Al content in the cellular environment might have caused the negative influence on the generation of ATP in neurons. Our previous observations also illustrated the negative impact of Al on the ATP‐producing machinery in oxygen‐consuming cells (Singla and Dhawan, ). Al treatment inhibited the activities of Ca 2+ ATPase and Na + /K + ATPase by directly interacting at the active binding sites of ATPases, indicating that Al altered cellular metabolism (Kaur and Gill, ; Silva et al, ; Singla and Dhawan, ).…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…In previous studies it has been reported that aluminum inhalation induced altered of expressions of glycogen synthase kinase-3 (GSK3) and protein phosphatase (PP1), which help in the regulation of carbohydrate metabolism in the rat's brain [87]. Mercury exposures in male marmoset monkey showed deposits of Hg in ventral horn motor neuron and atrophy of large myelinated motor axon [88].…”
Section: Neurotoxicity Of Metalsmentioning
confidence: 99%